Effects of wingwave® on athletes’ wellbeing and fluidity of gaze behavior - Weiland, Frank Peter Gadso; Noël, Benjamin; Klatt, Stefanie (Frontiers in Psychology, 2023)
Introduction The wingwave® method combining a muscular test and elements of eye movement desensitization and reprocessing has been found to successfully reduce anxiety and improve relaxation in people. However, it is still unclear how exactly its application improves individual wellbeing (though it is assumed to be related to changes in gaze patterns) and if it works for team sport athletes. Method To test both, team sport athletes who had reported a problem with a team sport aspect were randomly assigned to an experimental group and a control group. The experimental group members were individually coached by a wingwave® coach once while the other participants watched a tennis match instead. Results Results showed that athletes in the wingwave® group benefited from the coaching as their individual perception of their problems improved. These improvements were associated with a decrease of catch-up saccades in a visual object-tracking task conducted before and immediately after coaching. Discussion This points to wingwave® interventions affecting gaze behavior and consequently wellbeing of team sport athletes.